2020
DOI: 10.1097/tgr.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Aquatic Cycling for Treatment of Knee Osteoarthritis in Elderly People

Abstract: Objective: To assess the effects of aqua-cycling on pain, physical function, and muscle strength among elderly people with knee osteoarthritis. Methods: We performed a randomized controlled trial from November 2016 through July 2017 in an outpatient clinic of the Department of Physical Medicine and Rehabilitation at the University Hospital. Patients were 60 years and older and had knee osteoarthritis. Among 32 patients who were randomly allocated to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Their full texts were published in English from 2001 to 2020, representing 1592 (ranging from 24 to 302) knee osteoarthritis or hip osteoarthritis patients. Except for two studies [10,29] including males only, most of the studies showed a high percentage of female participants. The aquatic training periods ranged from 4 to 20 weeks except for one study [15] lasting 12 months, with a median of 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their full texts were published in English from 2001 to 2020, representing 1592 (ranging from 24 to 302) knee osteoarthritis or hip osteoarthritis patients. Except for two studies [10,29] including males only, most of the studies showed a high percentage of female participants. The aquatic training periods ranged from 4 to 20 weeks except for one study [15] lasting 12 months, with a median of 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies performed measurements at medium-term and long-term follow-ups after the whole aquatic training programs, two studies (Rezasoltani et al ., 2020 [29] and Azizi et al ., 2020 [10]) after 2 months, one (Lund et al .,2008 [14]) after 3 months, one (Taglietti et al ., 2018 [31]) after 4 months, two (Rewald et al ., 2020 [1] and Cochrane et al ., 2005 [15]) after 6 months and one (Waller et al ., 2017 [20]) after 16 months.…”
Section: Resultsmentioning
confidence: 99%
“…The exercise-induced hypoalgesia (EIH) activates afferent muscle A-delta and C fibers and the descending tract, where patients are distracted from the pain stimuli, thus, lowering pain sensitivity [26]. Furthermore, since the immersion depth is proportional to the percentage of weight bearing, buoyancy may help in pain alleviation during exercise [27,28]. The hydrostatic pressure compresses the tissues and, when combined with the circulatory changes that occur during immersion (non-weight bearing), lowers edema and allows for more movement, reducing joint and soft-tissue stiffness, thus, improving pain complaints [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, muscle activation function was determined by EMG or dynamic simulation 35 . Methods, which are easier to execute but less informative, such as isokinetic muscle strength tests and functional physical tests, were used in ve studies 12,13,32,37,38 .…”
Section: Methodsmentioning
confidence: 99%
“…An inappropriate sample size increases the risk of violating the normal distribution. Nine studies reported effect sizes using Cohen's d-statistic [26][27][28][29][30][31][32] or the Eta-squared statistic 12,33 . Most studies reported complete demographic information, but two studies did not report the age of the participants, and four studies did not report the body mass index (BMI) or weight and height.…”
Section: Assessment Of the Included Studiesmentioning
confidence: 99%